2017
DOI: 10.1111/1468-5973.12193
|View full text |Cite
|
Sign up to set email alerts
|

Sense‐making in social media during extreme events

Abstract: During an extreme event, individuals use social media to communicate, self‐organize, manage, and mitigate risks (crisis‐related communications) but also to make sense of the event (commentary‐related communications). This study focuses on commentary‐based social media communication practices of Twitter users to understand the processes and patterns of inter‐subjective sense‐making during an extreme event. We analyse Twitter communication generated during three events: The Sydney Lindt Café Siege (2014), the Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 36 publications
1
97
0
2
Order By: Relevance
“…They replaced several omitted variables, such as the owner of the page, the number of followers, and differences in usage habits between countries, each of which could affect the outcome. Previous research has established that com-munication patterns differ considerably between crises [51]. Unsurprisingly, the dummy variables had large coefficients, which shows that they indeed had a strong influence on the results.…”
Section: Discussionmentioning
confidence: 80%
“…They replaced several omitted variables, such as the owner of the page, the number of followers, and differences in usage habits between countries, each of which could affect the outcome. Previous research has established that com-munication patterns differ considerably between crises [51]. Unsurprisingly, the dummy variables had large coefficients, which shows that they indeed had a strong influence on the results.…”
Section: Discussionmentioning
confidence: 80%
“…Prior studies have shown that during crises and risk events, people engage in several forms of communication to learn about the specific situation, in order to gain control and reduce their personal uncertainties (Lachlan et al, 2016(Lachlan et al, , 2009). Social media platforms, such as Facebook or Twitter initially gained importance, as they became a highly utilized resource for communication and information seeking during crisis events (Stieglitz et al, 2017b). Acar and Muraki (2011) examined crisis communication on Twitter during the tsunami in Japan in 2011 and revealed that people who were directly involved, tweeted about their unsafe situation and survival related topics while people from indirectly related areas tweeted to inform others that they were safe.…”
Section: Crisis Communication In Social Mediamentioning
confidence: 99%
“…People publish situationally relevant information in social media sites based on their personal perceptions, activities, and what they gather from other media sites [17]. This enables the public to get insights into the situation first-hand close to real-time [17,36]. Moreover, news and media agencies publish real-time updates and announcements on Twitter during crisis events.…”
Section: Crisis Communication In Social Mediamentioning
confidence: 99%